EFEKTIVITAS PROGRAM KB DENGAN METODE OPERASI PRIA (MOP)/VASEKTOMI DI KABUPATEN SITUBONDO - Senain Senain; Hari Susanto; Arsya Chairul Fajri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2017)
The purpose of this research is to know the effectiveness of KB program implementation with MOP / Vasectomy in Situbondo Regency. The research method used qualitative approach. The data source is divided into two namely primary data and secondary data. Data collection uses observation, documentation and interviews. Data analysis consists of data reduction, data presentation, and conclusion or verification. Based on the results of the analysis showed that KB MOP (Male Operation Method) / Vasectomy in Situbondo Regency is ineffective and it is said because of socio-cultural condition of society that can not eliminate misperception of KB MOP program. The strategy set by the organizer that is Socialization to the community has not been fully implemented. There is no synchronization from the respective Party / Office concerned on Policy Formulation, Planning Process and Programming to the community. Infrastructure facilities of the MOP KB program, especially in Medical Personnel is still inadequate. Due to the limited number of medical workers involved in the MOP program KB is not effective and efficient.